A philosophy for the Romans: Cicero and the New Academy - Beltrão, Claudia (Romanitas - Revista de Estudos Grecolatinos, 2026)
In the last decades, Cicero has been reassessed as a significant and complex thinker due to the diversity and breadth of his writings across various literary genres, as well as his creative engagement with Hellenistic philosophy. Cicero’s work offers substantial insights into the intellectual life of the Mediterranean and late Republican Rome, as well as the production and circulation of knowledge during that time. This article will explore aspects of his intellectual landscape and how Cicero’s philosophical project is reflected in some of his forensic speeches and philosophical dialogues.
Keywords: Roman philosophy; New Academy; Pro Murena; In Pisonem; De finibus